Analisis Penerapan Hukum Wad‘i terhadap Akad Murābahah bil Wakālah dan Implikasinya pada Kepastian Hukum Syariah di Indonesia - Jaelani, Ihrom; Hasan, Mustofa; Gojali, Dudang (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2026)
This study aims to analyse the application of Al-Ḥukmu al-Waḍ‘ī to murabahah bil wakalah contracts and its implications for the certainty of Sharia law in Indonesia. The focus of the study is directed at the integration of causes, conditions, and legal obstacles in assessing the validity of contracts in Islamic banking practices, particularly at Bank Syariah Indonesia. The method used is library research with a qualitative-normative approach, through analysis of classical fiqh literature, DSN-MUI fatwas, and OJK regulations. The results of the study show that some murābaḥah bil wakālah practices do not fully comply with the causal structure of wad‘i law, because bank ownership is often administrative in nature and the sequence of contracts does not comply with sharia provisions. This has the potential to create legal uncertainty and weaken the legitimacy of sharia compliance. This study emphasises the importance of applying wad‘i law as an evaluative instrument in ensuring the validity of contracts and closing loopholes in legal non-compliance. Implicitly, sharia regulation and supervision need to be directed towards substantive validity so that the Islamic financial system is not only formally compliant, but also fair, moral, and in line with maqāṣid asy-syarī‘ah. Keywords: Al-Ḥukmu al-Waḍ‘ī, Murābaḥah bil Wakālah, Legal Certainty in Sharia, Sharia Compliance, Maqāṣid asy-Syarī‘ah.